Rancang Bangun E-Catering Pada CV. Lembaga Palembang - Muhammad Ridho Ardiansyah; Akhmad Sayuti; Nurhasanah (Jurnal Ilmiah Matrik, 2025)
The catering service sector in Palembang faces significant challenges in adapting to the digital era, particularly concerning operational efficiency and customer satisfaction. Manual business processes still implemented by CV. Lembaga, ranging from ordering to customer data management and delivery schedule arrangements, have proven to be time-consuming for consumers and potentially lead to errors. This research aims to design and develop a web-based e-catering system for CV. Lembaga Palembang as an innovative solution. Adopting the iterative cycle of the prototype method, this study involves stages of planning and requirements analysis, system design, initial prototype construction, testing and evaluation, and implementation. System design will be visualized using Unified Modeling Language (UML), including Use Case Diagrams for user functionality, Activity Diagrams for process flows, and Class Diagrams for data structures. This process aligns with the need for rapid validation and adaptation to changes. System acceptance by users will be analyzed using the Technology Acceptance Model (TAM), focusing on Perceived Usefulness and Perceived Ease of Use as key determinants of adoption. The resulting e-catering design is expected to automate CV. Lembaga's business processes , enhance operational efficiency , expand its market reach , and provide convenience, thereby improving customer satisfaction through integrated digital services.